Poging tot "n herdefinisie van die prediking binne die raamwerk van die Reformatiese teologie - Dreyer, T. F. J. (Hervormde teologiese studies, 1989)
An attempt to redefine praeching in terms of Reformational theology In the field of biblical studies and hermeneutics, modern research, in many aspects results in questioning the authority of the Bible as the Word of God. The consequences of these results often undermine preaching as the Word of God. Within the theology of the re formation , preaching is based upon sound exegetical study and expository of the biblical text. Hence scientific exegetical research brings the authority of preaching to a crisis. This paper is an attempt to redefine preaching in order to incorporate the results of modem research, as well as to conserve the fundamental concept of preaching as the Word of God.